2022
DOI: 10.4093/dmj.2021.0335
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus: Diagnostic Approaches and Maternal-Offspring Complications

Abstract: Gestational diabetes mellitus (GDM) is the most common complication during pregnancy and is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. GDM is associated with adverse pregnancy outcomes and long-term offspring and maternal complications. For GDM screening and diagnosis, a two-step approach (1-hour 50 g glucose challenge test followed by 3-hour 100 g oral glucose tolerance test) has been widely used. After the Hyperglycemia and Adverse Pregnancy Outcome study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 90 publications
(113 reference statements)
1
64
0
6
Order By: Relevance
“…e sum of the scores for the seven components was calculated for each participant, with a higher score indicating worse sleep quality. Sleep quality was classified according to the score achieved: poor (PSQI score of [16][17][18][19][20][21], general (PSQI score of [11][12][13][14][15], better (PSQI score of 6-10), and best (PSQI score of 0-5).…”
Section: Features Of the Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…e sum of the scores for the seven components was calculated for each participant, with a higher score indicating worse sleep quality. Sleep quality was classified according to the score achieved: poor (PSQI score of [16][17][18][19][20][21], general (PSQI score of [11][12][13][14][15], better (PSQI score of 6-10), and best (PSQI score of 0-5).…”
Section: Features Of the Prediction Modelmentioning
confidence: 99%
“…In particular, women with a history of GDM have a nearly 10-fold higher risk of type 2 diabetes than women with normoglycemic pregnancy [ 10 ]. For offspring, GDM is also associated with an increased risk of childhood obesity [ 11 ] and glucose intolerance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of other maternal organ dysfunction; liver involvement with or without right upper quadrant or epigastric abdominal pain, neurological complications; or hematological complications; or 3.uteroplacental dysfunction [13] . GDM was diagnosed after all women underwent a 75-g oral glucose tolerance test between 24 and 28 weeks of pregnancy, we also applied IADPSG criteria (one or more fasting, 1-h, or 2-h plasma glucose concentrations equal to or greater than threshold values of 5.1, 10.0, or 8.5 mmol/L, respectively) to diagnose GDM [14] . Early Preterm delivery, defined by a gestational age before 34 weeks.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…The incidence of GDM in China was reported to be 11.91% ( 3 ). Women with GDM are more likely to experience an adverse outcome, including Cesarean delivery, preeclampsia, soft issue injury of the birth canal, and severe maternal morbidity ( 4 ). An increasing number of studies have shown that women with a history of GDM are at an increased risk of being diagnosed as having type 2 diabetes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the short-term perinatal consequences associated with GDM, there are long-term complications for newborns. Studies have found that the risks of obesity, metabolic syndrome, type 2 diabetes, and impaired insulin sensitivity and secretion in offspring of mothers with GDM are 2- to 8-fold of those in offspring of mothers without GDM ( 4 ).…”
Section: Introductionmentioning
confidence: 99%